Aneuploidy and Ethanol Tolerance in Saccharomyces cerevisiae - Morard, Miguel; Macías, Laura G.; Adam, Ana C.; Lairón-Peris, María; Pérez-Torrado, Roberto; Toft, Christina; Barrio, Eladio (Frontiers in Genetics, 2019)
Response to environmental stresses is a key factor for microbial organism growth. One of the major stresses for yeasts in fermentative environments is ethanol. Saccharomyces cerevisiae is the most tolerant species in its genus, but intraspecific ethanol-tolerance variation exists. Although much effort has been done in the last years to discover evolutionary paths to improve ethanol tolerance, this phenotype is still hardly understood. Here, we selected five strains with different ethanol tolerances, and used comparative genomics to determine the main factors that can explain these phenotypic differences. Surprisingly, the main genomic feature, shared only by the highest ethanol-tolerant strains, was a polysomic chromosome III. Transcriptomic data point out that chromosome III is important for the ethanol stress response, and this aneuploidy can be an advantage to respond rapidly to ethanol stress. We found that chromosome III copy numbers also explain differences in other strains. We show that removing the extra chromosome III copy in an ethanol-tolerant strain, returning to euploidy, strongly compromises its tolerance. Chromosome III aneuploidy appears frequently in ethanol-tolerance evolution experiments, and here, we show that aneuploidy is also used by natural strains to enhance their ethanol tolerance.